Phosphoinositide 3-Kinase–Regulated Pericyte Maturation Governs Vascular Remodeling. Issue 7 (18th August 2020) - Figueiredo, Ana M.; Villacampa, Pilar; Diéguez-Hurtado, Rodrigo; José Lozano, Juan; Kobialka, Piotr; Cortazar, Ana Rosa; Martinez-Romero, Anabel; Angulo-Urarte, Ana; Franco, Claudio A.; Claret, Marc; Aransay, Ana María; Adams, Ralf H.; et al.
Abstract : Background: Pericytes regulate vessel stabilization and function, and their loss is associated with diseases such as diabetic retinopathy or cancer. Despite their physiological importance, pericyte function and molecular regulation during angiogenesis remain poorly understood. Methods: To decipher the transcriptomic programs of pericytes during angiogenesis, we crossed Pdgfrb(BAC)-CreER T2 mice into RiboTag flox/flox mice. Pericyte morphological changes were assessed in mural cell-specific R26-mTmG reporter mice, in which low doses of tamoxifen allowed labeling of single-cell pericytes at high resolution. To study the role of phosphoinositide 3-kinase (PI3K) signaling in pericyte biology during angiogenesis, we used genetic mouse models that allow selective inactivation of PI3Kα and PI3Kβ isoforms and their negative regulator phosphate and tensin homolog deleted on chromosome 10 (PTEN) in mural cells. Results: At the onset of angiogenesis, pericytes exhibit molecular traits of cell proliferation and activated PI3K signaling, whereas during vascular remodeling, pericytes upregulate genes involved in mature pericyte cell function, together with a remarkable decrease in PI3K signaling. Immature pericytes showed stellate shape and high proliferation, and mature pericytes were quiescent and elongated. Unexpectedly, we demonstrate that PI3Kβ, but not PI3Kα, regulates pericyte proliferation and maturation during vessel formation. Genetic PI3Kβ inactivation in pericytes triggered early pericyte maturation. Conversely, unleashing PI3K signaling by means of PTEN deletion delayed pericyte maturation. Pericyte maturation was necessary to undergo vessel remodeling during angiogenesis. Conclusions: Our results identify new molecular and morphological traits associated with pericyte maturation and uncover PI3Kβ activity as a checkpoint to ensure appropriate vessel formation. In turn, our results may open new therapeutic opportunities to regulate angiogenesis in pathological processes through the manipulation of pericyte PI3Kβ activity. Abstract : Supplemental Digital Content is available in the text.